Human Alu subfamilies and their methylation revealed by blot hybridization. - Schmid, C W (1991)
By a simple direct blot hybridization strategy, the existence of human Alu family subfamilies is confirmed. Using consensus restriction cleavage sites, individual bands can be resolved from genomic human DNA digests corresponding to three distinct Alu subfamilies. Digestion with methylation sensitive and insensitive restriction enzymes shows that the numerous CpG residues in the youngest Alu subfamilies are largely methylated in vivo, suggesting a model for the transcriptional regulation of Alu repeats.